1984
DOI: 10.1093/infdis/150.6.858
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Echovirus-12 in Volunteers: Determination of Minimal Infectious Dose and the Effect of Previous Infection on Infectious Dose

Abstract: A two-part study of echovirus-12 was done in volunteers. In the first part the human infectious dose of the virus was determined in 149 healthy adults with undetectable serum antibody, each of whom drank 0-330,000 plaque-forming units (pfu) of virus in 100 ml of nonchlorinated water. Infection was defined as fecal shedding of virus or significant (fourfold or greater) increases in serum antibody titer. The HID50 (i.e., the dose required for infection of 50% of the volunteers) was 919 pfu. Through statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 16 publications
1
28
0
1
Order By: Relevance
“…Of note, 50% of the positive samples were harvested during the January-June 2008 period (cases per 100,000 inhabitants: 13.3), 33% during July-December 2007 (cases per 100,000 inhabitants: 11.6), and the remaining 17% during January-June 2007 (cases per 100,000 inhabitants: 3.3). Addition- (34,36). Exposure dose was figured by applying the formula and parameters described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, 50% of the positive samples were harvested during the January-June 2008 period (cases per 100,000 inhabitants: 13.3), 33% during July-December 2007 (cases per 100,000 inhabitants: 11.6), and the remaining 17% during January-June 2007 (cases per 100,000 inhabitants: 3.3). Addition- (34,36). Exposure dose was figured by applying the formula and parameters described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the lack of a reliable cell system for the recovery of wild-type HAV, standardized quantitative molecular approaches, including appropriate quality assurance and quality control measures to assess the efficiency of critical steps in virus analysis, open the possibility of producing consistent and accurate exposure data (11). Additionally, the lack of an actual dose-response model for HAV makes it necessary to apply models developed for other enteric viruses (21,25,36,39).…”
mentioning
confidence: 99%
“…The infectious dose of a wild-type (unattenuated) nonpolio enterovirus administered by the natural route to a large number of susceptible individuals has also been determined under carefully controlled conditions in an isolation facility. The virus chosen for the study was echovirus 12, since it has not been associated with serious human illness (95). The HID 50 was 919 PFU.…”
Section: Properties Of the Enterovirusesmentioning
confidence: 99%
“…ECV11 Gregory and ECV12 Travis references strains were kindly obtained from the Virology Department of the Faculty of Medicine of Saint Etienne, France. Travis ECV12 prototype and strain belonging to serotype ECV2 (MON-ECV2) were chosen and included for comparison in this study because of their relatively avirulent phenotype as demonstrated in surveys of ECV prevalence from clinical samples and human challenge studies [46,47].…”
Section: Cells and Viral Strainsmentioning
confidence: 99%